2020
DOI: 10.3892/mco.2020.2143
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic toxicity during regorafenib treatment in patients with metastatic gastrointestinal stromal tumors

Abstract: Regorafenib is a multi-target tyrosine kinase inhibitor that has been approved for the treatment of metastatic colorectal cancer, advanced hepatocellular carcinoma, and metastatic gastrointestinal stromal tumors (GIST). Severe hepatobiliary toxicity has been reported in patients with colorectal cancer treated with regorafenib, but not in those with GIST. Therefore, the aim of the present study was to investigate the incidence and clinical course of regorafenib-associated hepatic toxicity (HT) in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Study drugs. The following drugs were used in the present study: Cisplatinum (Bristol Myers Squibb, New York, NY, USA) a standard first-line treatment for osteosarcoma; pazopanib (GlaxoSmithKline Plc., London, UK), an MKI approved for softtissue sarcoma and RCC (20); sunitinib (Pfizer Inc., New York, NY, USA), an MKI approved for gastrointestinal stromal tumors (GIST) and RCC (21); sorafenib (Bayer AG, Leverkusen, Germany), an MKI approved for RCC, HCC, and thyroid carcinoma (22); crizotinib (Pfizer Inc.), an MKI approved for non-small-cell lung cancer and anaplastic large-cell lymphoma (23); and regorafenib (Bayer AG), an MKI approved for metastatic colorectal cancer, GIST, and metastatic HCC (24).…”
Section: Methodsmentioning
confidence: 99%
“…Study drugs. The following drugs were used in the present study: Cisplatinum (Bristol Myers Squibb, New York, NY, USA) a standard first-line treatment for osteosarcoma; pazopanib (GlaxoSmithKline Plc., London, UK), an MKI approved for softtissue sarcoma and RCC (20); sunitinib (Pfizer Inc., New York, NY, USA), an MKI approved for gastrointestinal stromal tumors (GIST) and RCC (21); sorafenib (Bayer AG, Leverkusen, Germany), an MKI approved for RCC, HCC, and thyroid carcinoma (22); crizotinib (Pfizer Inc.), an MKI approved for non-small-cell lung cancer and anaplastic large-cell lymphoma (23); and regorafenib (Bayer AG), an MKI approved for metastatic colorectal cancer, GIST, and metastatic HCC (24).…”
Section: Methodsmentioning
confidence: 99%
“…Other frequently reported adverse events were diarrhea, fatigue, hoarseness, hypertension, and oral mucositis. One study [ 147 ] specifically investigated the incidence of regorafenib-associated hepatic toxicity, in which 5 of the 21 metastatic GIST patients developed (laboratory) hepatic toxicity. In a single-center retrospective study of 28 patients, toxicity and efficacy of regorafenib in fractioned dosing, 160 mg a day for the first 3 weeks of every 4-week cycle, was compared to continuous dosing of 120 mg a day.…”
Section: Resultsmentioning
confidence: 99%
“…An example compound showing the need for early, biologically relevant, safety assessment as well as efficacy testing was Regorafenib. This compound made it into clinical trials based on classical preclinical models, but was later found to cause hypertension [ 33 35 ] and hepatotoxicity [ 36 ] in the clinic. In our screen, the compound showed major anti-angiogenic efficacy ( Z * = − 17.7) but also showed significant toxicity (Medium toxicity).…”
Section: Discussionmentioning
confidence: 99%